2008
DOI: 10.1007/bf03182205
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of aerodynamic noise source around a rotating fan blade

Abstract: The purpose of this study is to understand the aerodynamic noise source distribution around a rotating fan blade by measuring the noise signal and velocity field around the blade. The local noise-level distribution over the fan blade is measured by microphone arrays, and the flow field is visualized by smoke and phase-averaged PIV measurement. The noise source distribution is examined by cross-correlation analysis between noise signal and velocity fluctuation. It is found that the noise source is located near … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The aeroacoustic characteristics of cooling fans are determined by their aerodynamics, such as flow separation, secondary flow and other special flow structures. A large number of studies have been performed on aerodynamic characteristics [3][4][5][6][7][8][9] and aeroacoustic characteristics [10][11][12][13][14][15][16]. For example, Nashimoto et al [3] used phase-averaged PIV measurement and found that the separation and reattachment of the flow occurred on the suction surface at the leading edge of the blade.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aeroacoustic characteristics of cooling fans are determined by their aerodynamics, such as flow separation, secondary flow and other special flow structures. A large number of studies have been performed on aerodynamic characteristics [3][4][5][6][7][8][9] and aeroacoustic characteristics [10][11][12][13][14][15][16]. For example, Nashimoto et al [3] used phase-averaged PIV measurement and found that the separation and reattachment of the flow occurred on the suction surface at the leading edge of the blade.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have been performed on aerodynamic characteristics [3][4][5][6][7][8][9] and aeroacoustic characteristics [10][11][12][13][14][15][16]. For example, Nashimoto et al [3] used phase-averaged PIV measurement and found that the separation and reattachment of the flow occurred on the suction surface at the leading edge of the blade. Marcus et al [4] found that the clearance flow flows out of the clearance and then towards the blade, resulting in strong pressure fluctuations at the tip of the blade.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the two-dimensional vortex method can predict the peak sound pressure levels from a centrifugal fan within a 4 dB-A deviation range of the measured sound. Nashimoto et al (2008) studied aerodynamic noise source distribution around a rotating blade by measuring the noise signal and velocity field around the blade. They showed that the noise signal closely correlates with velocity fluctuation, which indicates noise generation due to the formation of a vortex around the blade.…”
Section: Introductionmentioning
confidence: 99%
“…13 The causality correlation technique has been applied in the past by means of measuring the near-field fluctuations with various techniques. [13][14][15][16][17] Recent experiments [18][19][20][21][22][23] have shown that Particle-Image-Velocimetry (PIV) and microphone measurements can be used to obtain the cross correlation function between a near-field quantity and the acoustic pressure in the far-field. Using of the technique for the application orientated flow field around a slat presented here is the next step in the development of the causality correlation by means of PIV measurements in the near-field.…”
Section: Introductionmentioning
confidence: 99%